Fluopyram Sensitivity and Functional Characterization of SdhB in the Fusarium solani Species Complex Causing Soybean Sudden Death Syndrome - Sang, Hyunkyu; Witte, Alexander; Jacobs, Janette L.; Chang, Hao-Xun; Wang, Jie; Roth, Mitchell G.; Chilvers, Martin I. (Frontiers in Microbiology, 2018)
The succinate dehydrogenase inhibitor (SDHI) fungicide, fluopyram, is used as a soybean seed treatment to manage Fusarium virguliforme, the casual agent of sudden death syndrome (SDS). More recently, other species within clade 2 of the Fusarium solani species, F. tucumaniae in South America and F. brasiliense in America and Africa, have been recognized as additional agents capable of causing SDS. To determine if fluopyram could be used for management of SDS caused by these species, an in vitro sensitivity of the three Fusarium species to fluopyram was conducted. The mean EC50 values of F. brasiliense and F. virguliforme strains to fluopyram were 1.96 and 2.21 μg ml-1, respectively, but interestingly F. tucumaniae strains were highly sensitive (mean EC50 = 0.25 μg ml-1) to fluopyram compared to strains of the other two species. A sequence analysis of Sdh genes of Fusarium strains revealed that the F. tucumaniae strains contain an arginine at codon 277 in the SdhB gene instead of a glycine as in other Fusarium species. Replacement of glycine to arginine in SdhB-277 in a F. virguliforme wild-type strain Mont-1 through genetic transformation resulted in increased sensitivity to two SDHI fungicides, fluopyram and boscalid. Similar to a F. tucumaniae strain, the Mont-1 (SdhBG277R) mutant caused less SDS and root rot disease than Mont-1 on soybean seedlings with the fluopyram seed treatment. Our study suggests the amino acid difference in the SdhB in F. tucumaniae results in fluopyram being efficacious if used as a seed treatment for management of F. tucumaniae, which is the most abundant SDS causing species in South America. The establishment of baseline sensitivity of Fusarium species to fluopyram will contribute to effective strategies for managing Fusarium diseases in soybean and other pathosystems such as dry bean.